The Influence of Burnout and Job Satisfaction on Work-Life Balance in Part-Time Students of Buana Perjuangan Karawang University - Juniar, Juniar; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
The condition of studying while working is not something new in Indonesia. Challenges arise when students face burnout and require efforts to maintain a balance between job satisfaction in order to divide their time effectively between work and academic activities. The aim of this research is to examine the influence of burnout and job satisfaction on work-life balance. This research uses quantitative methods by collecting data from interviews and observations and distributing questionnaires. The data analysis technique uses SmartPLS 4 software. With a non-probability sampling technique using the Slovin formula, the sample results were 64 people from a total population of 173 with a total of 485 management students class of 2020, Buana Perjuangan University, Karawang. The results of hypothesis testing show that the variable el burnout has the original sample value worth -0.387 (negative), with P-Values worth 0.002, which means burnout has a influence negative and is significant to work-life balance. As well as Job satisfaction with work-life balance is worth 0.516. These values show that there is a positive correlation between job satisfaction and work-life balance. With this positive influence, it can be interpreted that the higher the level of job satisfaction, the more optimal work-life balance that can be achieved. On the other hand, if the level of burnout increases, the work-life balance that individuals may experience will be poor.